Interactions Between Ethanol and Dietary Fat in Determining Human Platelet Function - Fenn, Christopher G; Littleton, John M (Thrombosis and Haemostasis, 1984)
Platelet aggregation to collagen and ADP in vitro was assessed in the plasma of healthy human volunteers both before and after drinking 700 ml of white wine. This had no effect on platelet aggregation when compared with samples from the same individuals taken on a separate occasion without alcohol consumption. However, when alcohol was taken with a meal high in saturated fat, a significant inhibitory effect on platelet aggregation was observed when compared to the effect of the meal alone. There was no such interaction when the meal associated with alcohol ingestion contained mainly unsaturated fats. The fatty acid composition of plasma and platelet membranes from these volunteers showed a significantly increased proportion of saturated fats after the saturated fat meal. The concomitant ingestion of ethanol did not prevent this change. The concentration of alcohol in plasma achieved (c. 25 mM) may directly inhibit platelet aggregation when the platelet membrane content of saturated fats is high.
Keywords: Platelet aggregation; Ethanol; Saturated fats; Diet; Membranes